Optical solitons and other solutions to the Radhakrishnan-Kundu-Lakshmanan equation - Ozdemir, Neslihan; Esen, Handenur; Secer, Aydin; Bayram, Mustafa; Sulaiman, Tukur Abdulkadir; Yusuf, Abdullahi; Aydin, Huseyin (ELSEVIER GMBH, 2021)
Soliton theory has wide application in nonlinear physics fields with the inclusion of fluid dynamics, nonlinear fiber optics, plasma physics, and optics; thus, it has attracted much attention from researchers for the past few decades [1-3]. There are many mathematical models for propagation of soliton in the literature such as nonlinear Schro center dot dinger's equation [4,5], Chen-Lee-Liu equation [6], Schro center dot dinger-Hirota equation [7], Kundu-Eckhaus equation [8,9], Sasa-Satsuma equation [10-12], Manakov model [13,14], Kundu-Mukherjee-Naskar equation [15]. The gist of this paper is to examine the following perturbed and generalized RKL equations, given as. In this paper, the following perturbed and generalized RKL equations are considered, given as ( { iut+alpha uxx+beta F|u|2) ( } u=i sigma ux+i lambda F|u|2) {(|u|2)} ux + i mu Fxu - i gamma uxxx, This paper studies the perturbed Radhakrishnan-Kundu-Lakshmanan (RKL) equation and its special form, the generalized RKL equation. Kerr law nonlinearity is considered for both equations. The Riccati-Bernoulli sub-ODE technique is implemented to these nonlinear equations so that their optical solitons and complex wave solutions are retrieved. In order to derive a sequence of solutions of considered equations, Ba center dot cklund transformation can be carried out. 3D and 2D graphics of some solutions are depicted for chosen suitable parameters.
Keywords: Radhakrishnan-Kundu-Lakshmanan equation; Riccati-Bernoulli sub-ODE method; Optical soliton; Backlund transformation; PERTURBATION; Optics